Foamed silicone rubber and fireproof material composed of foamed silicone rubber

By using the foamed silicone rubber preparation method of A and B, the reaction speed is adjusted using a specific catalyst, the problems of high cost and insufficient fire resistance in the existing technology are solved, and the low-cost and high fire resistance are achieved. Silicone rubber is suitable for new energy vehicles, construction and nuclear power fields.

CN119463496APending Publication Date: 2025-02-18HUNAN BEISIFU NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411293824.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, foamed silicone rubber prepared using platinum catalyst is high in cost and has insufficient fire resistance. The two-component foamed silicone rubber has a high density and poor bonding performance, making it difficult to meet the high fire resistance in the fields of new energy vehicles, construction and nuclear power. Require.

Method used

Foamed silicone rubber is prepared using two components A and B. Component A includes α,ω-dihydroxypolysiloxane, hydroxy compounds and organometallic catalysts. Component B includes alkoxy-terminated polysiloxane With polymethylhydrogensiloxane, the reaction rate is adjusted to match the foaming and gel reaction through specific foaming reaction catalysts and organometallic catalysts, and the use of platinum catalysts is avoided.

Benefits of technology

It has achieved low-cost and high fire-resistant foamed silicone rubber, with low product density, excellent cell structure and high bonding performance, and is suitable for new energy vehicles, construction and nuclear power fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463496A_ABST
    Figure CN119463496A_ABST
Patent Text Reader

Abstract

The invention discloses foamed silicone rubber and a fireproof material composed of the foamed silicone rubber, and is characterized in that the foamed silicone rubber is composed of a component A and a component B. The component A comprises the following raw materials in parts by mass: 100 parts of alpha, omega-dihydroxy polysiloxane, 0.5-8 parts of a hydroxyl compound, 0.1-5 parts of a foaming reaction catalyst and 0.1-5 parts of an organic metal catalyst; the component B comprises 100 parts of alkoxy-terminated polysiloxane and 1-50 parts of polymethylhydrosiloxane, and the foaming reaction catalyst comprises one or a combination of two of diethylhydroxylamine and an organosilicon compound containing an amino oxygen group. The reaction ratio of the component A to the component B is (10: 1)-(1: 4). The bi-component foamed silicone rubber is low in manufacturing cost, capable of being stored for a long time, low in density, excellent in fireproof and flame-retardant performance, excellent in foam structure, excellent in bonding performance and convenient to prepare and construct on site.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application number 2024108734007, application date July 1, 2024, and name “A method for preparing foamed silicone rubber and fireproof material formed therefrom”. Technical Field

[0002] The present invention generally relates to a foamed silicone rubber and a fireproof material composed thereof, and more specifically, to a foamed silicone rubber material that can be advantageously applied to scenes such as battery packs of new energy vehicles, through holes or gaps in buildings, and nuclear power plants. Background Art

[0003] It is a major trend in the development of the automobile industry that new energy vehicles replace traditional fuel vehicles. New energy vehicles usually use aluminum alloy as the shell of the battery pack. Due to the poor heat resistance of aluminum alloy, it is usually necessary to coat the surface of the aluminum alloy battery pack with fireproof and heat-insulating materials to improve its fire resistance and safety performance. A large number of through holes are usually set in the walls or floors of buildings for cables, air ducts, gas pipes, etc. to pass through. In order to prevent the flame from spreading through the through holes in case of fire, it is usually necessary to use fireproof sealing materials to seal these through holes. In addition, in the high radiation environment of nuclear power plants, excellent sealing materials are usually required to seal important parts such as pipe connectors, pump valves, cable protective sleeves and seals. Foamed silicone rubber is a polyorganosiloxane porous polymer material. Because it not only has the high temperature resistance, flame retardancy, electrical insulation and radiation resistance of silicone rubber, but also has the advantages of light weight, heat insulation, flame retardancy and high porosity of foam materials, it is widely used as a sealing material in new energy vehicles, construction and nuclear power.

[0004] The Chinese invention patent application with publication number CN116478658A discloses an organic silicon absorbing foaming caulking material and a preparation method thereof. The caulking material is composed of component A and component B, wherein component A comprises: vinyl silicone oil, absorbing agent, hydroxy silicone oil, platinum catalyst, white carbon black, and liquid flame retardant, and component B comprises: vinyl silicone oil, hydrogen-containing silicone oil, absorbing agent, phenyl hydrogen-containing silicone resin, white carbon black, and inhibitor. Among them, the absorbing agent is a multilayer material obtained by coating an amino acid layer on the surface of a metal oxide and coating a silane coupling agent layer on the outside of the amino acid layer. The material has low density, uniform pores, low water absorption, and high magnetic permeability.

[0005] The Chinese invention patent application with publication number CN104559190A discloses a method for preparing a modified polysiloxane / two-component foamed silica composite material, which comprises the following specific steps: step 1: weighing α,ω-dihydroxy polydimethylsiloxane, adding white carbon black thereto, dehydrating and mixing at 140-160°C for 1-3h under 13-14kPa in a kneader to prepare a base material; step 2: taking the base material obtained in step 1, adding α,ω-dihydroxy polydimethylsiloxane, platinum-tetravinyltetramethylcyclotetrasiloxane and a microcapsule foaming agent of isobutane encapsulated by a polyvinyl chloride resin as an outer shell, mixing evenly at room temperature to obtain a component in the two-component silica gel. Step A; Step 3: Take the base material obtained in step 1, add methyl hydrogen polysiloxane and stir at room temperature to mix evenly to obtain component B in the two-component silica gel; Step 4: Mix boric acid and terminal hydroxyl polydimethylsiloxane, stir and treat at 120-200° C. for 2-7 hours to obtain boric acid-modified terminal hydroxyl polydimethylsiloxane; Step 5: Mix the boric acid-modified terminal hydroxyl polydimethylsiloxane obtained in step 4 with component A obtained in step 2, stir evenly to obtain a mixture; Step 6: Mix the mixture obtained in step 5 with component B obtained in step 3, and carry out a cross-linking foaming reaction to obtain a modified polysiloxane / two-component foamed silica gel composite material.

[0006] In the technology with publication number CN116478658A, platinum catalyst is used for catalysis. On the one hand, platinum is a precious metal with high cost, so the product is difficult to promote; on the other hand, as a fireproof material, foamed silicone rubber needs to add flame retardants such as nitrogen, phosphorus, chlorine and other elements to improve the fire resistance, and these elements will poison the platinum catalyst and cause it to fail. Therefore, using platinum catalysts, it is difficult to prepare two-component foamed silicone rubber with high fire resistance and flame retardant properties to meet the high fire protection requirements in the fields of new energy, construction and nuclear power. In addition, the density of the foamed silicone rubber prepared by this technology is usually greater than 0.5g / cm 3 , resulting in more foamed silicone rubber material being needed to fill the same volume of voids, which also leads to higher costs.

[0007] In the technology with publication number CN104559190A, the presence of microcapsules can alleviate the phenomenon of reduced foaming ratio due to storage to a certain extent. However, this method needs to be prepared at a high temperature of more than 70°C. Since it is difficult to perform heating operations on site, it is not suitable for application scenarios such as building fireproof sealing, caulking or battery pack filling.

[0008] In addition, in situations such as sealing cable or pipe penetration holes in walls or floors, the existing two-component foamed silicone rubber still has the problem of poor adhesion to cables, pipes and other penetrations. In other situations where high air tightness and water tightness are required, the existing two-component foamed silicone rubber is usually difficult to meet the technical requirements, and coupling agents, interface agents and other substances must be applied to the surface to be bonded in advance to achieve good bonding.

[0009] In order to solve the problems existing in the prior art, the present invention provides an innovative two-component foamed silicone rubber and a fireproof material composed thereof. The present invention also provides a preparation method of the foamed silicone rubber. Summary of the invention

[0010] The present invention provides a foamed silicone rubber and a fireproof material composed thereof, which not only has low manufacturing cost, excellent pore structure, low product density, high bonding performance, and good fire retardancy, but also can be stored for a long time and is convenient for on-site construction, and can be advantageously applied to scenes such as battery packs of new energy vehicles, through holes of buildings, and nuclear power plants. The present invention also provides a method for preparing the foamed silicone rubber.

[0011] The present invention adopts the following scheme to solve the problems existing in the prior art and achieve the above-mentioned invention objectives.

[0012] According to one embodiment of the present invention, a foamed silicone rubber is provided, characterized in that it consists of two components A and B, where, by weight of raw materials, component A comprises 100 parts of α,ω-dihydroxypolysiloxane, 0.5 to 8 parts of hydroxyl compounds, 0.1 to 5 parts of foaming reaction catalysts, and 0.1 to 5 parts of organometallic catalysts; component B comprises 100 parts of alkoxy-terminated polysiloxane and 1 to 50 parts of polymethylhydrogensiloxane, and the foaming reaction catalyst comprises one or a combination of two of diethylhydroxylamine and aminooxy-containing organosilicon compounds.

[0013] Generally, the preparation process of two-component foaming materials mainly involves two chemical reactions, one is the foaming reaction and the other is the gel reaction. Only when the reaction rates of the foaming reaction and the gel reaction are properly matched, can a foam material with good performance be obtained. In the present invention, a specific foaming reaction catalyst is used to catalyze the condensation reaction of hydroxyl compounds and polymethyl hydrogen siloxane to produce hydrogen as the main foaming reaction, and an organic metal catalyst is used to catalyze the condensation cross-linking reaction of α, ω-dihydroxy polysiloxane and alkoxy-terminated polysiloxane as the gel reaction. On the one hand, the reaction rate between α, ω-dihydroxy polysiloxane and polymethyl hydrogen siloxane is reduced, and the gel reaction rate between α, ω-dihydroxy polysiloxane and alkoxy-terminated polysiloxane is enhanced, which facilitates the matching between the foaming reaction rate and the gel reaction rate; on the other hand, the increase in manufacturing cost caused by the use of platinum catalysts and the poisoning of catalysts in the presence of flame retardants are avoided, which is conducive to the preparation of foamed silicone rubber with high fire resistance and flame retardant properties.

[0014] According to one embodiment of the present invention, the alkoxy-terminated polysiloxane in the B component is a straight-chain polysiloxane containing 1 to 3 alkoxy groups at each end, and the active alkoxy group undergoes a condensation reaction with the terminal hydroxyl group of the α,ω-dihydroxy polysiloxane in the A component under the catalysis of an organic metal catalyst to cross-link into a network polymer gel.

[0015] Polymethyl hydrogen siloxane is also commonly referred to as hydrogen-containing silicone oil, wherein the higher the hydrogen content, the stronger the reaction activity. According to one embodiment of the present invention, the hydrogen content of the polymethyl hydrogen siloxane is 0.1 to 1.6 wt%. Preferably, the hydrogen content of the polymethyl hydrogen siloxane is 1 to 1.6 wt% of polymethyl hydrogen siloxane.

[0016] According to one embodiment of the present invention, the reaction ratio of component A to component B is a mass ratio of 10:1 to 1:4, and the reaction ratio is adjusted by using α,ω-dihydroxy polysiloxanes of different viscosities, alkoxy-terminated polysiloxanes, and polymethyl hydrogen siloxanes of different hydrogen contents. Preferably, the reaction ratio of component A to component B is a mass ratio of 2:1 to 1:2. More preferably, the reaction ratio of component A to component B is a mass ratio of 1:1 to 1:2.

[0017] According to one embodiment of the present invention, the viscosity range of the α,ω-dihydroxy polysiloxane is 10 to 6000 cSt at 25°C, the viscosity range of the alkoxy-terminated polysiloxane is 10 to 10000 cSt at 25°C, and the hydrogen content of the polymethyl hydrogen siloxane is 0.1 to 1.6 wt%.

[0018] According to one embodiment of the present invention, the hydroxy compound includes one or more combinations of water, low-viscosity hydroxy silicone oil, monohydric alcohol, dihydric alcohol, polyhydric alcohol, phenolic compounds, and carboxylic acid compounds.

[0019] According to one embodiment of the present invention, preferably, the foaming reaction catalyst is diethylhydroxylamine.

[0020] According to one embodiment of the present invention, the organometallic catalyst comprises a combination of one or more of an organotin catalyst, an organobismuth catalyst, and an organozinc catalyst. Preferably, the organometallic catalyst comprises an organotin catalyst. More preferably, the organometallic catalyst is dibutyltin dilaurate.

[0021] According to one embodiment of the present invention, the amount of the organometallic catalyst is 0.5 to 5 parts. Preferably, the amount of the organometallic catalyst is 1 to 4 parts. Preferably, the amount of the organometallic catalyst is 1 to 2 parts.

[0022] According to one embodiment of the present invention, the component A and / or component B further comprises 1 to 100 parts of polydimethylsilicone oil, calculated by weight of raw materials.

[0023] According to one embodiment of the present invention, the polydimethylsilicone oil is used to adjust the viscosity of the B component and the reaction ratio of the A component and the B component.

[0024] According to one embodiment of the present invention, the component A and / or the component B further comprises 10 to 230 parts of a flame retardant, based on the mass of the raw materials. Alternatively, the component A comprises 10 to 230 parts of a flame retardant, and the component B does not comprise a flame retardant. Alternatively, the component A comprises 5 to 80 parts of a flame retardant, and the component B comprises 5 to 150 parts of a flame retardant. Alternatively, the component A does not comprise a flame retardant, and the component B comprises 5 to 150 parts of a flame retardant.

[0025] According to one embodiment of the present invention, the flame retardant includes a combination of one or more of ammonium polyphosphate, expandable graphite, melamine, melamine phosphate, aluminum hydroxide, zinc borate, magnesium hydroxide, phosphate flame retardant, and phosphate flame retardant. Preferably, the flame retardant includes a combination of ammonium polyphosphate, expandable graphite, aluminum hydroxide, and melamine. More preferably, the A component includes ammonium polyphosphate and expandable graphite, and the B component includes aluminum hydroxide and melamine.

[0026] According to one embodiment of the present invention, the component A and / or the component B further comprises 5 to 50 parts of a leveling agent, based on the mass of the raw materials. Alternatively, the component A comprises 5 to 50 parts of a leveling agent, and the component B does not comprise a leveling agent. Alternatively, the component A comprises 2.5 to 25 parts of a leveling agent, and the component B comprises 2.5 to 25 parts of a leveling agent. Alternatively, the component A does not comprise a leveling agent, and the component B comprises 5 to 50 parts of a leveling agent.

[0027] Preferably, the component A comprises 5 to 20 parts of a foam leveling agent. More preferably, the component A comprises 5 to 10 parts of a foam leveling agent.

[0028] According to one embodiment of the present invention, the foam leveling agent is activated calcium carbonate. Preferably, the foam leveling agent is nano-activated calcium carbonate. Optionally, the average particle size of the nano-activated calcium carbonate is between 10 and 100 nm. Optionally, the average particle size of the nano-activated calcium carbonate is between 70 and 90 nm. By introducing the nano-activated calcium carbonate, the foam structure can be stabilized and the foam can be leveled.

[0029] According to one embodiment of the present invention, the component A further comprises 0.5 to 1.5 parts of an inhibitor, based on the mass of the raw materials. By adding an inhibitor to the component A to inhibit the catalytic activity of the organotin catalyst, the organobismuth catalyst, and the organozinc catalyst, the shelf life of the component A can be extended. In addition, by changing the amount and type of the inhibitor, the coordination of the foaming reaction and the gelling reaction can also be balanced and adjusted. The inhibitor evaporates along with the hydrogen during the foaming process, so that the gelling reaction catalyst gradually recovers its catalytic activity, catalyzes the gelling reaction, and forms a balance and coordination with the foaming reaction in terms of speed, so as to obtain a higher foaming multiple and a uniform and fine pore structure.

[0030] According to one embodiment of the present invention, the inhibitor includes organic acid, β-diketone compound, and isocyanate compound.

[0031] According to one embodiment of the present invention, the A component and / or the B component further comprises 0.5 to 5 parts of pigment, based on the mass of the raw materials. Alternatively, the A component comprises 0.4 to 5 parts of pigment, and the B component does not comprise pigment. Alternatively, the A component comprises 0.25 to 2.5 parts of pigment, and the B component comprises 0.25 to 2.5 parts of pigment. Alternatively, the A component does not comprise pigment, and the B component comprises 0.5 to 5 parts of pigment.

[0032] According to one embodiment of the present invention, the pigment is iron red.

[0033] According to one embodiment of the present invention, the component A and / or the component B further comprises 0.5 to 10 parts of a reinforcing agent, based on the mass of the raw materials. Alternatively, the component A comprises 0.5 to 10 parts of a reinforcing agent, and the component B does not comprise a reinforcing agent. Alternatively, the component A comprises 0.5 to 5 parts of a reinforcing agent, and the component B comprises 0.5 to 5 parts of a reinforcing agent. Alternatively, the component A does not comprise a reinforcing agent, and the component B comprises 0.5 to 10 parts of a pigment.

[0034] According to one embodiment of the present invention, the reinforcing agent includes one or more of fumed silica, precipitated silica, carbon black, and nano-titanium dioxide. Alternatively, the reinforcing agent is silane-treated fumed silica.

[0035] According to another embodiment of the present invention, there is provided a fireproof material made of the foamed silicone rubber as described in any one of claims 1-9.

[0036] According to another embodiment of the present invention, there is provided a mixing device for preparing the foamed silicone rubber as described in any one of claims 1 to 9, which comprises a two-component glue bottle and a static mixer connected to the two-component glue bottle, the two-component glue bottle comprises a first chamber and a second chamber which are independent of each other, and the static mixer comprises a first air inlet.

[0037] Optionally, the mixing device further comprises a conversion head, wherein the conversion head is connected between the two-component glue bottle and the static mixer, and the conversion head comprises a second air inlet.

[0038] Optionally, the mixing device further comprises a material conveying extension pipe, wherein the material conveying extension pipe is connected to a material discharge port of the static mixer, and the material conveying extension pipe comprises a third air inlet.

[0039] According to another embodiment of the present invention, there is provided a method for preparing the foamed silicone rubber, comprising: Step 1: Use a high-speed disperser to prepare component A and component B respectively; Step 2: Weigh component A and component B respectively according to a reaction ratio of 1:1 to 1:10 by mass, then put component A into the first chamber of the two-component glue bottle, and put component B into the second chamber of the two-component glue bottle; Step 3: Use a glue gun to extrude component A and component B, and mix them in a static mixer, while introducing compressed gas into the first air inlet of the static mixer and / or the second air inlet of the adapter and / or the third air inlet of the material conveying extension tube; Step 4: Extrude the mixed component A and component B and let them stand for foaming.

[0040] In the present invention, component A and component B of the foamed silicone rubber are respectively loaded into the first chamber and the second chamber of a two-component rubber bottle, and compressed air is introduced into the mixture while mixing them in a static mixer, so that, on the one hand, part of the compressed air can be dissolved in the mixed liquid or adsorbed on the surface of the powder particles in the mixed liquid to form bubble nuclei, which is conducive to foaming and forming uniform and fine bubbles; on the other hand, the disturbance of the compressed air in the static mixer forms a shear force, which can effectively solve the problem of powder precipitation formed by long-term storage, increase the mixing effect of component A and component B, and the introduction of a large amount of compressed air can quickly take away the volatile inhibitor, so that the organic metal catalyst can quickly restore its activity, and timely catalyze the condensation reaction of alkoxy-terminated polysiloxane and α,ω-dihydroxy polysiloxane to form a gel.

[0041] According to the foamed silicone rubber and the fireproof material composed thereof of the present invention, the following beneficial technical effects can be obtained.

[0042] First, the present invention uses the reaction of condensation of hydroxyl compounds and polymethyl hydrogen siloxane to generate hydrogen as the main foaming reaction, reduces the reaction rate between α, ω-dihydroxy polysiloxane and polymethyl hydrogen siloxane, enhances the gel reaction rate between α, ω-dihydroxy polysiloxane and alkoxy-terminated polysiloxane, and facilitates the matching between the foaming reaction rate and the gel reaction rate.

[0043] Second, the present invention avoids the use of expensive platinum catalysts, so that not only more flame retardants can be selected to flame retard the foamed silicone rubber without causing catalyst poisoning and deactivation, which can greatly reduce costs; and relatively low viscosity α, ω-dihydroxy polysiloxane can be reacted with alkoxy-terminated polysiloxane to form a polymer gel with relatively high viscosity, making it possible to prepare high-quality foamed silicone rubber using low viscosity α, ω-dihydroxy polysiloxane, thereby broadening the application of foamed silicone rubber; in addition, the introduction of alkoxy-terminated polysiloxane can give the foamed silicone rubber excellent bonding properties.

[0044] Third, the present invention introduces compressed air into the mixture of component A and component B, which can solve the problem of reduced expansion ratio, increased density and reduced pore structure quality caused by long-term storage of component A and component B.

[0045] Fourthly, the present invention introduces nano-active calcium carbonate, which can stabilize the foam structure and make the foam uniform.

[0046] Fifth, the foamed silicone rubber prepared by the present invention has excellent performance, especially the fireproof material composed thereof can be advantageously used in scenes such as battery packs of new energy vehicles, through holes of buildings and nuclear power plants. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Attached Figure 1This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 1 of the present invention at a magnification of 35.

[0048] Attached Figure 2 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 2 of the present invention at a magnification of 35.

[0049] Attached Figure 3 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 3 of the present invention at a magnification of 35.

[0050] Attached Figure 4 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 4 of the present invention at a magnification of 35.

[0051] Attached Figure 5 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 5 of the present invention at a magnification of 35.

[0052] Attached Figure 6 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 6 of the present invention at a magnification of 35.

[0053] Attached Figure 7 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 7 of the present invention at a magnification of 35.

[0054] Attached Figure 8 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 8 of the present invention at a magnification of 35.

[0055] Attached Fig. 9 is an optical microscope photograph of a cross section of the foamed silicone rubber prepared according to Example 9 of the present invention at a magnification of 35.

[0056] Attached Fig.10 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 10 of the present invention at a magnification of 35.

[0057] Attached Fig.11 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Example 11 of the present invention at a magnification of 35.

[0058] Attached Fig.12 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Comparative Example 1 at a magnification of 35.

[0059] Attached Fig.13 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Comparative Example 2 at a magnification of 35.

[0060] Attached Fig.14This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Comparative Example 3 at a magnification of 35.

[0061] Attached Fig.15 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Comparative Example 4 at a magnification of 35.

[0062] Attached Fig.16 This is an optical microscope photograph of the cross section of the foamed silicone rubber prepared according to Comparative Example 5 at a magnification of 35.

[0063] Attached Fig.17 Schematic diagram of a foaming silicone rubber mixing device according to an embodiment of the present invention.

[0064] Attached Fig.18 is a schematic diagram of a foaming silicone rubber mixing device according to another embodiment of the present invention. DETAILED DESCRIPTION

[0065] In order to better illustrate the present invention, some embodiments are listed below, but it should be understood that these embodiments are not intended to limit the present invention.

[0066] For the present invention, the following terms are used in this specification: "~" includes the two values ​​before and after it, for example, 5~10 means greater than or equal to 5 and less than or equal to 10; "cm", "mm" and "nm" represent the length units centimeter, millimeter and nanometer, respectively; "g" means the mass unit gram; "h" indicates the time unit hour; "℃" indicates the temperature unit Celsius; "cSt" means the unit of kinematic viscosity, centistokes; "g / cm 3 " indicates density in grams per cubic centimeter; "Hydroxy compounds" refer to alcohols, phenols, silanols, and carboxylic acid compounds that contain the functional group hydroxyl (-OH) in the molecule. Water is the hydroxyl compound with the smallest molecular weight.

[0067] In addition, unless otherwise specified, all material parts are based on mass, and material viscosity is the value measured at 25°C.

[0068] Attached Fig.17 and 18: is a schematic diagram of a foaming silicone rubber mixing device according to an embodiment of the present invention. As shown in the figure, the foaming silicone rubber mixing device includes a two-component glue bottle 1 and a static mixer 2 connected to the two-component glue bottle, the two-component glue bottle 1 includes a first chamber 11 and a second chamber 12 that are independent of each other, and the static mixer 2 includes a first air inlet 21. When in use, the first chamber 11 and the second chamber 12 of the two-component glue bottle 1 are respectively filled with component A and component B of the foaming silicone rubber. When the component A and the component B are mixed in the static mixer 2, compressed gas is introduced into the static mixer 2 through the first air inlet 21. Optionally, the compressed gas includes one or a combination of several of air, carbon dioxide, nitrogen, and argon.

[0069] Optionally, as shown in the figure, the mixing device may further include a conversion head 3, which is connected between the two-component glue bottle 1 and the static mixer 2, and includes a second air inlet 31 and a mixing chamber 32. The A component and the B component are mixed with the compressed gas introduced from the second air inlet 31 in the mixing chamber 32, and then enter the static mixer 2 for further mixing, and the compressed gas is introduced into the second air inlet 31.

[0070] Optionally, the mixing device further comprises a material conveying extension pipe 4, the material conveying extension pipe 4 is connected to the discharge port of the static mixer 2, and the material conveying extension pipe 4 comprises a third air inlet 41. When the A component and the B component are mixed in the static mixer 2, compressed gas is introduced into the third air inlet 41.

[0071] Raw material selection: α,ω-dihydroxypolysiloxane uses α,ω-dihydroxypolydimethylsiloxane with a kinematic viscosity of 3000cSt, the hydroxy compound uses low-viscosity hydroxy silicone oil with a kinematic viscosity of 30cSt, the foaming reaction catalyst uses diethylhydroxylamine, the organic metal catalyst uses dibutyltin dilaurate, the polymethylhydrogensiloxane uses hydrogen-containing silicone oil with a hydrogen content of 1.6%, the alkoxy-terminated polysiloxane uses trimethoxy-terminated polydimethylsiloxane with a kinematic viscosity of 1000cSt, the flame retardant uses a combination of ammonium polyphosphate, expandable graphite, aluminum hydroxide, and melamine, the nano-activated calcium carbonate uses calcium carbonate with an average particle size of less than 100nm and surface treated, and the reinforcing agent is silane-treated fumed silica.

[0072] Preparation method description: Method 1: In the first step, component A and component B are prepared separately using a high-speed disperser; in the second step, component A and component B are weighed according to the reaction ratio, added into a plastic beaker, stirred for 30 seconds using a stirrer with a dispersion disk, and then allowed to stand for foaming after stirring; Method 2: In the first step, use a high-speed disperser to prepare component A and component B respectively; in the second step, weigh component A and component B according to the reaction ratio, respectively put them into two connected single bottles of the same size of a two-component glue bottle, use a glue gun to extrude, enter into a static mixer for mixing, and stand for foaming after extrusion; Method 3: The first step is to use a high-speed disperser to prepare component A and component B respectively; the second step is to weigh component A and component B according to the reaction ratio, and put them into two connected single bottles of the same size of a two-component glue bottle respectively, use a glue gun to extrude them, and enter them into a static mixer for mixing. At the same time, compressed air is introduced before the static mixer, and the components are left to stand for foaming after extrusion.

[0073] Simple apparent density test method: After the prepared foam is cured at room temperature for 24 hours, cut out 3 cubes with a side length of about 2 cm. Measure the size to an accuracy of 0.01 cm, weigh the weight to an accuracy of 0.01 g, and divide the weight by the volume to obtain the apparent density to an accuracy of 0.01 g / cm 3 .

[0074] Foam structure evaluation method: Use an optical microscope to magnify 35 times, observe the flat cross-section of the foam, and evaluate the foam structure according to the grades listed in Table 1:

[0075] Qualitative evaluation method for foam bonding performance: insert a 15cm long and 3cm diameter PVC sheathed cable into the mixed material, wait for the foaming to be completed and cure at room temperature for 24 hours, observe the bonding between the foamed silicone rubber and the cable, and evaluate the foam structure according to the grades listed in Table 2:

[0076] Storage time: If materials A and B are mixed and foamed immediately after preparation, the storage time is marked as 0 days; if materials A and B are stored for 30 days after preparation and then mixed and foamed, the storage time is marked as 30 days, and so on.

[0077] Examples 1-11 and Comparative Examples 1-5.

[0078] Examples 1-11 were prepared according to the formula and method shown in Table 3. The apparent density, cell structure and bonding properties of the obtained foamed silicone rubber are shown in Table 3:

[0079] Comparative Examples 1-5 were prepared according to the formula and method shown in Table 4. The apparent density, pore structure and bonding properties of the obtained foamed silicone rubber are shown in Table 4:

[0080] Compared with Comparative Examples 1-5, Example 1-11 simultaneously introduces trimethoxy-terminated polydimethylsiloxane and catalyst dibutyltin dilaurate, so that trimethoxy-terminated polydimethylsiloxane and α,ω-dihydroxy polydimethylsiloxane form a gel with moderate viscosity under the catalysis of catalyst dibutyltin dilaurate, which helps to form a stable and uniform foam, and greatly enhances the bonding performance of foam silicone rubber and cables. From the experimental results, the products obtained according to Examples 1-11 basically achieve excellent results in terms of apparent density, pore structure and bonding performance. The products obtained in Comparative Examples 1-5 basically have a high density, poor pore structure, and poor bonding performance.

[0081] Examples 1, 5, 6 and 7 and Comparative Examples 4 and 5.

[0082] Except for the different parts of the catalyst dibutyltin dilaurate, the formula, reaction ratio and storage time of Examples 1, 5, 6 and 7 are the same; except that Example 5 is prepared using Method 3, Examples 1, 6 and 7 are all prepared using Method 1. From the experimental results, as the number of catalyst parts increases, the apparent density of the product first decreases and then increases, and the apparent density in Example 5 is the smallest, and then the apparent density begins to increase again. It can be seen that when the amount of catalyst increases, the gel viscosity increases too fast, and the foaming reaction cannot match it, resulting in an increase in density.

[0083] Comparative Example 4 did not use a catalyst. From the experimental results, the density of the prepared foamed silicone rubber was relatively large, about 42% higher than that of Example 1, and the pore structure and bonding performance were also poor, indicating that in the absence of dibutyltin dilaurate catalysis, trimethoxy-terminated polydimethylsiloxane and α,ω-dihydroxypolydimethylsiloxane could not react to form a gel, resulting in a relatively large density, poor pore structure, and the bonding property was also related to the formation of the gel.

[0084] Comparative Example 5 is based on Example 1 without the trimethoxy-terminated polydimethylsiloxane. From the experimental results of Comparative Examples 4 and 5 and Examples 1, 5, 6 and 7, it can be seen that in the absence of alkoxy-blocking polysiloxane, foamed silicone rubber with excellent pore structure and bonding properties cannot be obtained.

[0085] Examples 1 and 2.

[0086] The difference between Examples 1 and 2 is that Example 1 adds nano-active calcium carbonate. From the experimental results, the density of the foamed silicone rubber of Example 1 is lower and the pores are finer and denser. It can be seen that nano-active calcium carbonate has a relatively obvious foam stabilizing and uniform foaming effect. The foam stabilizing and uniform foaming effect of nano-active calcium carbonate can also be seen from the experimental results of Comparative Examples 1 and 2, and the density of Comparative Example 1 is also lower and the pores are also finer and denser.

[0087] Examples 1, 3, 4, 5.

[0088] The formula and reaction ratio of Examples 1, 3, 4, and 5 are the same. The storage time of Example 1 is 0 days, and the storage time of Examples 3, 4, and 5 is 30 days. Examples 1 and 3 are prepared using Method 1, and Examples 4 and 5 are prepared using Method 2 and Method 3, respectively. From the experimental results, after Example 3 was stored for 30 days, it was prepared using Method 1, and the foam cell structure obtained was good, but it was worse than the excellent cell structure obtained by Example 1 after 0 days of storage, and the density was also increased by 15%; Example 4 was prepared using Method 2, and the foam density was large and the cell structure was poor; Example 5 was prepared using Method 3, and a foam with very low density (15% lower than Example 1), excellent cell structure, and excellent bonding performance can be obtained. It can be seen from this that the mixing method of introducing compressed air can solve the disadvantage of increased density caused by storage, especially for the packaging method of two-component glue bottles.

[0089] Although the present invention has been described through the above-mentioned specific embodiments, it should be understood that the foregoing description does not limit the scope of protection of the present invention to the above-mentioned specific embodiments. On the contrary, the foregoing description is intended to indicate that the scope of protection of the present invention determined by the claims includes the above-mentioned specific embodiments and their equivalents.

Claims

1. A foamed silicone rubber, characterized in that: It is composed of two components, A and B. Calculated by the mass of raw materials, component A includes 100 parts of α,ω-dihydroxy polysiloxane, 0.5-8 parts of hydroxyl compounds, 0.1-5 parts of foaming reaction catalysts, and 0.1-5 parts of organic metal catalysts; component B includes 100 parts of alkoxy-terminated polysiloxane and 1-50 parts of polymethyl hydrogen siloxane. The foaming reaction catalyst includes one or a combination of diethylhydroxylamine and aminooxy-containing organic silicon compounds.

2. The foamed silicone rubber according to claim 1, characterized in that Calculated by weight of raw materials, component A and / or component B further comprises 10 to 230 parts of flame retardant.

3. The foamed silicone rubber according to claim 2, characterized in that: The flame retardant includes one or more combinations of ammonium polyphosphate, expandable graphite, melamine, melamine phosphate, aluminum hydroxide, zinc borate, magnesium hydroxide, phosphate ester flame retardant, and inorganic phosphate flame retardant.

4. The foamed silicone rubber according to claim 1, characterized in that: Calculated by weight of raw materials, component A and / or component B further comprises 1 to 100 parts of polydimethylsilicone oil.

5. The foamed silicone rubber according to claim 1, characterized in that: Calculated by weight of raw materials, component A and / or component B further comprises 5 to 20 parts of a uniform foaming agent, wherein the uniform foaming agent is nano-active calcium carbonate.

6. The foamed silicone rubber according to any one of claims 1 to 5, characterized in that: Calculated by weight of raw materials, component A and / or component B also includes 0.5 to 10 parts of reinforcing agent.

7. The foamed silicone rubber according to any one of claims 1 to 5, characterized in that: The organometallic catalyst includes one or more combinations of organotin catalysts, organobismuth catalysts, and organozinc catalysts.

8. The foamed silicone rubber according to claim 7, characterized in that: The amount of the organic metal catalyst is 1 to 2 parts.

9. The foamed silicone rubber according to any one of claims 1 to 5, characterized in that: The reaction ratio of the component A to the component B is 10:1 to 1:4 by mass.

Citation Information

Patent Citations

  • Preparation method of modified polysiloxane / double-component foamed silicone composite material

    CN104559190A

  • Organosilicon wave-absorbing foaming joint filling material and preparation method thereof

    CN116478658A